PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MTs PADA MATERI FUNGSI KUADRAT MELALUI MODEL PEMBELAJARAN THINK PAIR-SHARE (TPS) - Maryam Firdaus; M. Afrilianto (IKIP Siliwangi, 2021)
This research was conducted to determine how the influence of the Think-Pair-Share (TPS) cooperative model on the communication skills of students at MTS Negeri 1 Cimahi, especially in the quadratic function material. Classroom Action Research of often called Classroom Action Research (CAR) is a method used in this research with the hope that it will provide information or how to improve the abilities of the teacher and student activeness in the learning process. In this research, the subjects were MTSN 1 Cimahi class IX-D students with a total of 33 students. The test is an instrument used in this study, with data processing techniques based on the average percentage of all students scores then compared with the minimum completeness criteria (KKM) in MTSN 1 Cimahi of 75. The result of the test based on the research that has been done, namely the TPS cooperative learning model have an effect on the increase in students comunication skill where there is a significant increase in the pre-cycle result of the students average score of 35,2 then after implementing cycle 1 learning, the average result of student experience an increase of 78. Based on the results obtained, it can be concluded and said that the research that has been done is complete because it has reached the desired target. Classes that have implemented the TPS cooperative learning model can create a more lively classroom atmosphere because it requires students to be active and creative during the learning process. So, this proves that the TPS cooperative model can improve student 'communication skills and students' learning completeness with quadrta function material in class IX-D MTSN 1 Cimahi.